PEMAHAMAN HOLISTIK TENTANG HUKUM WARIS ISLAM: PERSPEKTIF FILOSOFIS - Muchamad Coirun Nizar; Rozihan Rozihan (Indonesian Journal of Islamic Literature and Muslim Society, 2018)
The Islamic law of inheritance has a very important position in the development of Islamic law. The Islamic law Scholars 'and Quranic Commentators discussed many of these issues, from the classical period to the present day. Philosophy with its three branches: ontology, epistemology, and axiology are often used as a method to understand the nature of something. This article presents the discussion on the philosophical perspective of Islamic law of inheritance in order to obtain a holistic understanding. The Islamic law of inheritance ontologically is the Shari'ah of Allah to the Muslims as the provisions that must be implemented in accordance with those contained in the Qur'an and Hadith. This Islamic law with its various provisions has a binding legal force for all Muslims to run it. Epistemologically, the Islamic law of inheritance is a series of provisions from Allah derived from the Qur'an, hadith, and ijtihad by Salaf scholars. Whereas axiologically, the  Islamic law of inheritance has a certain purpose i.e. granting heir rights to the heirs according to their proportions.